Infiltration and extravasation of intravenous infusions in children-value of high-quality care on outcome - Huang Litao; Ren Yuxuan; Shu Yongxia (Journal of the Pakistan Medical Association, 2021)
Objective: To study the value of high-quality care on the outcome of infiltration and extravasation of peripheral intravenous infusions in children. Methods: After ethical approval for this retrospective cohort study, we conducted secondary data analysis on data collected on children <3 years, hospitalized in the Third Affiliated Hospital of Zunyi Medical University between January 2013 and September 2019. The study population was divided into control and high-quality care groups. The outcomes were severity of infiltration and extravasation of intravenous infusions graded by INS (Infusion Nurses society score). Ordinal logistic regression was used to evaluate the independent relationship of high-quality care and infiltration and extravasation, as well as to identify risk factors associated with the outcome of infiltration and extravasation. Results: During the study period, 2147 and 14121 children were assigned to the control and high-quality care groups, respectively. The ordinal logistic regression analysis showed that, compared with the control group, the high-quality care group had a lower severity of infiltration and extravasation (odds ratio (OR): 0.75, 95% confidence interval (CI): 0.63-0.90). Additionally, the multivariable model also identified that the causes of infiltration and extravasation include agents with high osmolarity, poor condition of veins, guardianship negligence, and allergies to dressing materials. Conclusion: High-quality care was more effective in reducing the incidence and degree of infiltration and extravasation of peripheral intravenous infusions than the routine care given to the controls. Therefore, the high-quality care program is worth continuing. Keywords: Children; extravasation; infiltration; nurse; Continuous...